When hell came to Texas - Vaughan, Robert, 1937- (Pocket Books, 2013)
In the days after the Civil War, a solitary rider travelled the open frontier, but he wasn't alone, for Death seemed to travel with him. Or maybe it was the Devil himself who gave him the lethal pistol shot that earned him the name Death's Acolyte. And when the stranger with the scarred face, who calls himself Ken Casey, rode into the peaceful Texas town of Wardell, maybe peace for his own ravaged soul was all he wanted. But in Wardell, all hell is about to break loose. Awaiting a train shipment of gold, Angus Pugh and his army of outlaws, including notorious gunslinger Luke Draco, take the town hostage and kill a few innocent citizens as a lesson to any comers. Donning priestly vestments, Ken Casey, ordained man of the cloth, steps from the shadows to conduct the victims funeral rites and that's just his first revelation. For Casey can destroy souls as easily as he saves them, and earthly justice is delivered in gun smoke and blood.